Radar Target Characteristics Extraction using Polarization Scattering Matrix - L Vijaya Lakshmi; A Jaya Lakshmi; M N V S S Kumar; P Sirish Kumar (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Now a day’s characterization of targets using radar is very important in Air Traffic Control, Defense, and Stealth etc.  In order to know the characteristics of the target it is very essential to know the polarization properties of that particular target which depends upon scattering nature of the target.  The polarization properties are important for radar target besides amplitude, phase and frequency. The polarization may be potentially used to improve target detection, anti-interference, and radar target recognition. Polarization properties of a target can be obtained using polarization scattering matrix (PSM). In this paper the polarization matrix of various geometrical shapes are derived.  For radar target recognition (RTR), a method using properties of the polarization scattering matrix (PPSM) is presented in this paper. A dipole has been considered to calculate the polarization matrix and polarization properties. The properties of the polarization scattering matrix: the determinant, Trace of Power Scattering Matrix, Depolation, Eigen polarization angle and Module of Polarization Ellipticity are analyzed. These properties are analyzed for different orientation angles of the targets.